Identification of Black Spots Based on Reliability Approach - Ghaffari, Ahmadreza; Kashani, Ali Tavakoli; Moghimidarzi, Sayedbahman (Promet - Traffic&Transportation, 2013)
Identifying crash “black-spots”, “hot-spots” or “high-risk” locations is one of the most important and prevalent concerns in traffic safety and various methods have been devised and presented for solving this issue until now. In this paper, a new method based on the reliability analysis is presented to identify black-spots. Reliability analysis has an ordered framework to consider the probabilistic nature of engineering problems, so crashes with their probabilistic na -ture can be applied. In this study, the application of this new method was compared with the commonly implemented Frequency and Empirical Bayesian methods using simulated data. The results indicated that the traditional methods can lead to an inconsistent prediction due to their inconsider -ation of the variance of the number of crashes in each site and their dependence on the mean of the data.